Proton MR Spectroscopy of Polymicrogyria and Heterotopia - Widjaja, Elysa; Griffiths, Paul D.; Wilkinson, Iain D. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Proton MR spectroscopy of the brain allows noninvasive in vivo assessment of metabolites, which may be useful in understanding the biology of malformations of cortical development. The aim of this study was to determine the MR spectroscopic characteristics of polymicrogyria and heterotopia compared with those of normal frontal lobe white matter.METHODS: We recruited 22 patients with radiographic findings characteristic of polymicrogyria, nine patients with radiographic findings characteristic of heterotopia, and 10 control subjects into the study. The MR imaging technique consisted of high-spatial-resolution axial dual-echo and gradient-echo 3D volume imaging. A single-voxel point-resolved technique (1600/135 [TR/TE]) was used to acquire spectra from the region of neocortical malformation and from frontal lobe white matter in control subjects. The differences in N-acetyl moieties (NA)/creatine (Cr), NA/choline (Cho), and Cho/Cr ratios among patients with heterotopia, those with polymicrogyria, and control subjects were compared by using the Kruskal-Wallis test followed by the Mann-Whitney U (Wilcoxon) test.RESULTS: No statistically significant differences were noted in the NA/Cr, NA/Cho, and Cho/Cr ratios between the polymicrogyria group and controls, the heterotopia group and controls, or the polymicrogyria and heterotopia groups.CONCLUSION: Both heterotopia and polymicrogyria are malformations of cortical development that occur at a relatively late stage of brain development. The neurons and glia in these lesions are mature, and the metabolites appear to be similar to those of normal adult frontal white matter.